1984
DOI: 10.1161/01.str.15.2.376
|View full text |Cite
|
Sign up to set email alerts
|

Decreased incidence and mortality of stroke.

Abstract: SUMMARY Dr. Whisnant argues persuasively that control of hypertension has played a major role in the decline of stroke.' He offers a cohesive and logical overview on this decline and does so with data from his own vast experience and with the advantages of the Mayo Clinic system which includes a centralized population-based diagnostic index, neurological expertise and a high autopsy rate. However, neither Dr. Whisnant's arguments nor the Mayo Clinic data justify the conclusion that "treatment of hypertension i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…Our study confirmed the increased risk of Cl in cases with hypertensive and rheumatic heart diseases [1,2,[4][5][6][7], It is noteworthy that rheumatic heart disease became signifi cant when hypertension was excluded in the analysis. The association we observed be tween transient ischemic attacks and Cl has also been reported by others [2,5,6,17],…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study confirmed the increased risk of Cl in cases with hypertensive and rheumatic heart diseases [1,2,[4][5][6][7], It is noteworthy that rheumatic heart disease became signifi cant when hypertension was excluded in the analysis. The association we observed be tween transient ischemic attacks and Cl has also been reported by others [2,5,6,17],…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirms the known associa tion of all three types of stroke with hyper tension and arteriosclerosis, which has been observed in prospective studies [1,2,[4][5][6][7][13][14][15][16][17], Diabetes mellitus was confirmed as a risk factor as well as obesity, which is related to both hypertension and glucose in tolerance [1,6,18].…”
Section: Discussionsupporting
confidence: 88%
“…Whisnant (1984) suggests that the treatment of hypertension may be the only significant contributor to the decline of stroke mortality. Hachinski (1984), in contrast, argues that a reduction in causes of death associated with stroke, such as heart disease, may account for the decline.…”
Section: Cause-specific M O Rta Lity Trends From 1 9 6 8 To 1 9 8mentioning
confidence: 99%
“…Also important in interpreting mortality patterns was the potential significance of dependent competing risks. That is, for several diseases mortality rates appeared to have declined because of an association with another chronic condition whose m ortality rate had declined (Hachinski 1984). Given the high prevalence of m ultiple chronic conditions at advanced ages such cause dependency is potentially a very important factor in mortality changes.…”
mentioning
confidence: 99%
“…Even though its incidence has decreased, 12% of global hospi talization are due to stroke [ 1 ]. Recently, a decline in long term mortality due to stroke has been reported [2]. In con trast, neither short-term survival nor primary morbidity strictly related to cerebral damage have been reduced by any therapy.…”
Section: Introductionmentioning
confidence: 99%